Media personnel in education : a competency approach - Chisholm, Margaret E. 4 0 16; Ely, Donald P.; 5 (Englewood Cliffs, N.J. : Prentice-Hall, 1976)
A reference textbook based on functions performed by media professionals. Each function and its related competencies are described.
Includes bibliographies and index.
Keywords: 2 -- 0; 6; Instructional materials personnel.;Librarians.; 20; 2